Differential effects of the type of iron chelator on the absolute number of hematopoietic peripheral progenitors in patients with β-thalassemia major - Gian Luca Forni; Marina Podestà; Marco Musso; Giovanna Piaggio; Khaled M. Musallam; Manuela Balocco; Sarah Pozzi; Alessandra Rosa; Francesco Frassoni (Haematologica, 2013)
Several studies have established an association between iron chelation therapy with deferasirox and hematopoietic improvement in patients with myelodysplastic syndromes. There are no data from patients with β-thalassemia major. In a cross-sectional study, we evaluated the absolute number of several hematopoietic peripheral progenitors (colony-forming unit-granulocyte/macrophage, erythroid burst-forming units, colony-forming unit-granulocyte/erythrocyte/macrophage/megakaryocyte, and long-term culture-initiating cells) in 30 patients with β-thalassemia major (median age 29.5 years, 40% males) and 12 age-matched controls. For the β-thalassemia major patients, data on splenectomy status, the type of iron chelator used, and serum ferritin levels reflecting changes in iron status on the chelator were also retrieved. All patients had to be using the same iron chelator for at least 6 months with >80% compliance. The absolute number of all hematopoietic peripheral progenitors was higher in β-thalassemia major patients than in controls, and varied between splenectomized and non-splenectomized patients (lower number of erythroid burst-forming units and higher numbers of colony-forming unit-granulocyte/macrophage, colony-forming unit-granulocyte/erythrocyte/macrophage/megakaryocyte, and long-term culture-initiating cells). The number of erythroid burst-forming units was significantly higher in patients taking deferasirox (n=10) than in those taking either deferoxamine (n=10) or deferiprone (n=10) (P